ANALISIS KESULITAN SISWA KELAS IV DALAM MENYELESAIKAN MASALAH SOAL CERITA MATERI POLA BILANGAN DI SD - Hernaeny, Ulfah; Simanjuntak, Parulian; Nadirah, Nadirah; Aprillia, Sabila; Pramasti, Aliza; Bada, Sitti Sastriana (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
This study aims to analyze the difficulties experienced by fourth-grade students of SD Islam Al-Falaah in solving word problems on number patterns, the factors causing these difficulties, and strategies to reduce them based on Newman’s five stages, namely reading, comprehension, transformation, process skills, and writing the final answer. The research employed a qualitative descriptive approach with fourth-grade students as the subjects, who were given five mathematics word problems. Data were collected through written tests, interviews, and observations. The results indicate that the lowest level of difficulty occurred at the reading stage (8.7%), followed by difficulties in understanding the problem (13.4%), transformation (18.1%), and process skills (22.8%). The highest level of difficulty was found at the stage of writing the final answer (36.9%). These difficulties were influenced by weak mastery of basic arithmetic operations, low understanding of number patterns, difficulties in comprehending the language used in the problems, as well as a lack of accuracy, independence, and self-confidence. Efforts to overcome these difficulties included providing varied and contextual exercises, implementing enjoyable learning through educational games, applying scaffolding strategies, and using guiding questions and constructive feedback to enhance students’ motivation and independence. ABSTRAK Penelitian ini bertujuan untuk menganalisis kesulitan siswa kelas IV SD Islam Al-Falaah dalam menyelesaikan soal cerita materi pola bilangan, faktor penyebab kesulitan, serta strategi untuk mengurangi kesulitan berdasarkan lima tahap Newman, yaitu kesulitan membaca, memahami, transformasi, keterampilan proses, dan penulisan jawaban akhir. Penelitian menggunakan pendekatan deskriptif kualitatif dengan subjek siswa kelas IV yang diberikan lima soal cerita matematika. Teknik pengumpulan data meliputi tes tertulis, wawancara, dan observasi. Hasil penelitian menunjukkan bahwa kesulitan paling rendah terjadi pada tahap membaca sebesar 8,7%, diikuti kesulitan memahami soal sebesar 13,4%, kesulitan transformasi sebesar 18,1%, dan kesulitan keterampilan proses sebesar 22,8%. Kesulitan tertinggi terdapat pada tahap penulisan jawaban akhir sebesar 36,9%. Kesulitan siswa dipengaruhi oleh lemahnya penguasaan operasi hitung dasar, rendahnya pemahaman pola bilangan, kesulitan memahami bahasa soal, serta kurangnya ketelitian, kemandirian, dan kepercayaan diri. Upaya yang dilakukan untuk mengatasi kesulitan tersebut meliputi pemberian latihan yang bervariasi dan kontekstual, pembelajaran yang menyenangkan melalui permainan edukatif, penerapan strategi scaffolding, serta pemberian pertanyaan pemantik dan umpan balik konstruktif guna meningkatkan motivasi dan kemandirian siswa.